2019
DOI: 10.1002/jcp.28082
|View full text |Cite
|
Sign up to set email alerts
|

Receptor activity‐modifying protein 1 regulates the phenotypic expression of BMSCs via the Hippo/Yap pathway

Abstract: Receptor activity‐modifying protein 1 (RAMP1) might be a critical regulator during bone wound healing. However, the roles and mechanisms of RAMP1 in osteogenesis remain unclear. Here, we aimed to elucidate the role of RAMP1 and explore the effects of Yes‐associated protein 1 (Yap1), an effector of the Hippo/Yap pathway, in this process. We used a RAMP1 overexpression lentiviral system in bone marrow mesenchymal stem cells (BMSCs), which enhanced RAMP1 expression in an effective, appropriate, and sustained mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
2
19
0
1
Order By: Relevance
“…CGRP promotes the proliferation and osteogenic activity of both osteoblasts and their precursor cells in a dose-dependent manner, as observed in primary osteoblastic cells isolated from the calvaria of newborn rabbits, by increasing the levels of intracellular cAMP and upregulating expression of activating transcription factor (45). The Hippo/Yap pathway is also involved in the osteogenic phenotype mediated by the G-protein coupled receptor RAMP1 (46). Coupling with osteogenesis, CGRP exerts an angiogenic effect in the early stage during bone regeneration and ischemia, partly due to its vasodilator capacity and stimulation of endothelial cell migration (11,47).…”
Section: Neuropeptides Of the Sensory Nervous Systemmentioning
confidence: 87%
See 1 more Smart Citation
“…CGRP promotes the proliferation and osteogenic activity of both osteoblasts and their precursor cells in a dose-dependent manner, as observed in primary osteoblastic cells isolated from the calvaria of newborn rabbits, by increasing the levels of intracellular cAMP and upregulating expression of activating transcription factor (45). The Hippo/Yap pathway is also involved in the osteogenic phenotype mediated by the G-protein coupled receptor RAMP1 (46). Coupling with osteogenesis, CGRP exerts an angiogenic effect in the early stage during bone regeneration and ischemia, partly due to its vasodilator capacity and stimulation of endothelial cell migration (11,47).…”
Section: Neuropeptides Of the Sensory Nervous Systemmentioning
confidence: 87%
“…CGRP is a nociceptive neurotransmitter released from capsaicin-sensitive sensory nerves in response to various stimulations ( 6 , 13 , 43 ). The CGRP receptor complex contains the calcitonin receptor-like receptor and its co-receptor, receptor activity modifying protein 1 (RAMP1); expression of these receptor complexes have been demonstrated on osteoclasts, osteoblasts and their precursors, and BMMs ( 44 46 ). Although the distribution of CGRP positive fibers in skeleton is similar to that of SP ( 7 ), they do not exert similar functions in bone metabolism.…”
Section: Neuropeptides Of the Sensory Nervous Systemmentioning
confidence: 99%
“…There is strong evidence indicates that BMSCs are regulated by some biological signals on differentiation into bone tissue via Hippo-YAP pathway. The knockout of GNAS activates Hippo signaling pathway and eventually suppresses osteogenic differentiation of BMSCs (An et al, 2019), consistently, through the regulation of Hippo-YAP signaling pathway RAMP1 can promote the osteogenesis process of BMSCs that induced by CGRP (Zhang et al, 2019). Tang and Weiss (2017) revealed an interaction of Snail/Slug and YAP/TAZ, which regulates the differentiation ability of BMSCs in a cooperative way, suggesting a potential impact on the properties of osteogenesis.…”
Section: The Influence Of Hippo-yap Signaling On Osteogenesismentioning
confidence: 95%
“…Our published studies showed that fendiline significantly inhibits proliferation, survival and metastatic characteristics of PDAC cells, as evident by reduced migration, invasion and anchorage independent growth [40]. In the current study we tested if combining fendiline with the YAP1 inhibitor visudyne (Verteporfin), which is used for photodynamic therapy of macular degeneration, [41,42,43,44,45,46], elicits additive inhibitory effects on survival and metastatic characteristics of PDAC cells. Additionally, experiments were also conducted with combinations of fendiline and gemcitabine, the nucleoside analog commonly used to treat PDAC.…”
Section: Introductionmentioning
confidence: 99%